Development of new large pod Trombay groundnut (Arachis hypogaea) selections - KALE, D M; BADIGANNAVAR, A M; MURTY, G S S (The Indian Journal of Agricultural Sciences, 2013)
In ground nut (Arachis hypogaea L.), cultivars with large pod and early maturity are rare. By crossing a selection 'TG 19' having large pods, low yield and dormancy with high yielding eultivars 'TAG 24' and 'TG 26' 8 true breeding selections with large kernels, designated as TGLPS 1-8 were established in F5 generation. In the evaluation trials for 4seasons, theyÂ  showed superior yield over the large kernel checks, 'TKG 19A' and 'BAU 13'. To confirm their superiority for large kernel size, studies were made by taking 100-kernel weight and also by image analysis. Among the 8 selections TGLPS 2, 3, and 7 were found to have all desirable traits such as early maturity, high yield, and greater proportion ofIarge kernels (>=80g 100) and lacked dormancy. Due to lower oil content, they may suit for table purpose and fit into local cropping systems due to early maturity and absence of dormancy. Further evaluation of these selections will be done in the co-ordinated varietal trials.